THE DESIGN OF DEBURRING AIDS TO INCREASE THE PRODUCTION EFFICIENCY OF KN0081 SPACERSAT PT. XYZ - Andrian, Yohanes Oscar; Zefanya Rangga Prangestya2; Sutrisno; Yohanes Nugroho; Archi Kun Cahyo Utomo (Magister Teknik Mesin Universitas Pancasila, 2025)
Deburring is one of the important production processes in part manufacturing. Spacer KN0081 is one of the parts of the fuel bracket protractor that functions as a distance guard between the bracket and components in the car engine system. The focus of the deburring process is the quality of the deburring and the cycle time of the process. The quality and efficiency of the deburring process can be improved by using tools for the deburring process. The design of the deburring tool uses a collet clamping mechanism and an interlock system. The spacer is clamped using a collet, then deburred. The interlock mechanism allows the adjustment of the tool's rotation angle to facilitate the setting process. The research method used is VDI 2221 as a design tool and SOLIDWORKS software as a device for creating the design. The best variant design was selected based on technical and economic assessments resulting in a design solution for the deburring spacer product KN0081. The result of the process cycle time analysis is 0.55 minutes for the processing of 1 spacer. Based on cycle time analysis calculations, deburring tools can improve spacer quality and reduce deburring process cycle time to 80% more efficient.